Analisis Tafsir QS An-Nahl Ayat 64 Menurut Quraish Shihab: Takhrij Hadits di Era Teknologi AI sebagai Petunjuk dan Rahmat - Usvatun Khasanah; Abdul Matin Bin Salman (Journal of Innovative and Creativity, 2025)
This study examines the tafsir QS An-Nahl ayat 64 according to Muhammad Quraish Shihaband its relation to the implementation of takhrij hadits in the era of artificial intelligence (AI)technology. The verse emphasizes the function of the Qur'an as guidance and mercy for thebelievers, aiming to clarify disputes among people in religious matters. The research employsa qualitative method with a library research approach and content analysis, as well as acomparative study between traditional takhrij hadits methods and modern AI-based methods.The results show that AI technology is capable of accelerating and strengthening the scientificverification of hadiths, making AI a new instrument of guidance and mercy aligned with themeaning of the verse. Thus, the synergy between classical interpretation and technologicaladvancement can enrich Islamic scientific methodology and facilitate an authentic andapplicable understanding of religious teachings